2016
DOI: 10.1186/s13037-016-0114-9
|View full text |Cite
|
Sign up to set email alerts
|

Is immediate weight bearing safe for periprosthetic distal femur fractures treated by locked plating? A feasibility study in 52 consecutive patients

Abstract: BackgroundPeriprosthetic distal femur fractures associated with total knee replacement are increasing in incidence. We hypothesized that a standardized management protocol would result in few implant failures and a low rate of postoperative complications.MethodsRetrospective observational cohort study at an urban level 1 trauma center and academic level 2 trauma center. Consecutive patients with periprosthetic distal femur fractures and stable total knee arthroplasty were included between January 1, 2011 and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 30 publications
0
45
0
5
Order By: Relevance
“…As the practice of the study location was to make all patients non-weightbearing for a minimum of 6 weeks, analysis was not possible in this regard. Although non-weightbearing is commonly the practice followed in many centres, recent studies [7, 46] have shown successful outcomes including high union rates in patients allowed full weightbearing after locked plating of distal femoral fractures. Although no biomechanical proof currently exists, there may be a beneficial effect on fracture site biology from weightbearing.…”
Section: Discussionmentioning
confidence: 99%
“…As the practice of the study location was to make all patients non-weightbearing for a minimum of 6 weeks, analysis was not possible in this regard. Although non-weightbearing is commonly the practice followed in many centres, recent studies [7, 46] have shown successful outcomes including high union rates in patients allowed full weightbearing after locked plating of distal femoral fractures. Although no biomechanical proof currently exists, there may be a beneficial effect on fracture site biology from weightbearing.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies limited to PDFFs have employed weight-bearing restrictions of duration 6–12 weeks [ 9 , 10 , 20 ]. One previous study of 52 patients allowing immediate unrestricted weight-bearing after minimally invasive LLP fixation reported a favourable reoperation rate of 5/54 (9%) [ 24 ]. Although this previous study did not include a RWB group for comparison, this reoperation figure compares favourably with both that in the current study and those in studies where weight-bearing restrictions were applied: Lotzien et al [ 9 ] n = 45, reoperation rate 22%; Hoellwarth et al [ 10 ], n = 87, reoperation rate 10%; Ruder et al [ 20 ], n = 35, reoperation rate 6%.…”
Section: Discussionmentioning
confidence: 99%
“…In studies limited to patients with PDFFs, postoperative weight-bearing status has either been restricted [ 9 , 20 ] or not reported [ 10 ]. The safety of unrestricted weight-bearing after LLP fixation of PDFFs has been reported by Smith et al [ 24 ], although no comparative group was included.…”
Section: Introductionmentioning
confidence: 99%
“…However, even this frequently performed operation is associated with complications. Femoral fractures like fissures of the proximal femur are a frequent intraoperative complication [ 2 ], especially in the presence of limited bone quality (osteopenia or osteoporosis) in geriatric patients [ 3 , 4 ]. There is a trend away from cemented towards uncemented femoral stem fixation, further increasing the risk of intraoperative proximal femoral fractures (IPFF) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%